Pendidikan Karakter Dalam Pembentukkan Akhlak Mulia Di MTS ISTIQLAL DELITUA - Sarah Audry Lubis; Zuliana (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This PKP activity is one of the subjects that must be taken for students who take the level or degree of an undergraduate education study program. This PKP activity was carried out covering several stages, namely the preparation stage and the implementation stage, starting from observation, learning, consultation, teacher guidance, and preparation of learning tools including: lesson plans, syllabus, modules, teacher workbooks, and learning media. At this time the author was entrusted with the responsibility of teaching the material